A Cyclometalated Iridium(III) Complex Serves as a Phosphorescent Probe for Specific Mitochondrial Imaging in Living Cells. Issue 6 (8th March 2016) - Wang, Jinquan; Hou, Xiaojuan; Jin, Chengzhi; Chao, Hui
Abstract: A new cyclometalated iridium(III) complex [Ir(2‐pq)2 (HPIP)]Cl (Ir1, 2‐pq=3‐phenylisoquinoline, HPIP=2‐(2‐hydroxyphenyl)imidazo[4, 5‐f]1, 10‐phenanthroline) was synthesized and applied to image mitochondria in living cells.Ir1 displayed excellent ability to selectively accumulate in mitochondria of live cells with no requirement of replacement of the culture medium. Due toIr1 exhibiting better photostability than the commercially available mitochondrial trackers, this complex could be applicable for the imaging and tracking of the mitochondrial morphological changes over long periods of time. In addition, in vitro cytotoxicity investigation revealed thatIr1 showed negligible cytotoxicity at the concentrations employed. Based on these, Ir1 is suitable for organelle‐selective imaging in living cells. Abstract : A new cyclometalated iridium(III) [Ir(2‐pq)2(HPIP)]Cl (Ir1, 2‐pq=3‐phenylisoquin‐ oline, HPIP=2‐(1H‐imidazo[4, 5‐f][1, 10]phenanthrolin‐2‐yl) phenol), exhibited excellent photophysical properties and was developed to image mitochondria in living cells.